Early-life tobacco smoke elevating later-life osteoporosis risk: Mediated by telomere length and interplayed with genetic predisposition - Dongsheng Di; Haolong Zhou; Zhangbo Cui; Jianli Zhang; Qian Liu; Tingting Yuan; Tingting Zhou; Xiao Luo; Danyang Ling; Qi Wang (Journal of Advanced Research)
Introduction: The growing prevalence of osteoporosis (OP) in an aging global population presents a significant public health concern. Tobacco smoke negatively affects bone turnover, leading to reduced bone mass and heightened OP and fracture risk. However, the impact of early-life tobacco smoke exposure on later-life OP risk remains unclear. Objectives: This study was to explore the effects of early-life tobacco smoke exposure on incident OP risk in later life. The mediating role of telomere length (TL) and the interaction with genetic predisposition were also studied. Methods: Data on in utero tobacco smoke exposure (IUTSE) status and age of tobacco use initiation from the UK Biobank were used to estimate early-life tobacco smoke exposure. Incident OP cases were identified according to health-related records. Linear, Cox, and Laplace regression models were mainly used for data analysis. Results: Individuals with IUTSE showed a higher OP risk [hazard ratio (HR): 1.06, 95 % confidence interval (CI): 1.01, 1.11] and experienced earlier OP onset by 0.30 years [50th percentile difference = -0.30, 95 % CI: −0.51, −0.09] compared to those without. Participants initiating tobacco smoke in childhood, adolescence, and adulthood had 1.41 times (95 % CI: 1.23, 1.61), 1.17 times (95 % CI:1.10, 1.24), and 1.14 times (95 % CI: 1.07, 1.20) the risk of OP, respectively, compared to never smokers. They also experienced earlier OP onset by 2.16, 0.95, and 0.71 years, sequentially. The TL significantly mediated the early-life tobacco exposure and OP association. Significant joint and interactive effects were detected between early-life tobacco smoke exposure and genetic elements. Conclusions: Our findings implicate that early-life tobacco smoke exposure elevates the later-life OP risk, mediated by telomere length and interplayed with genetic predisposition. These findings highlight the importance of early-life intervention against tobacco smoke exposure and ageing status for precise OP prevention, especially in individuals with a high genetic risk.